EXERCISE GUIDELINES FOR PATIENTS WITH OBESITY: COMPARATIVE EFFECTIVENESS OF TRAINING MODALITIES AND CLINICAL CONSIDERATIONS - Worasettawat, Tunyakarn; Ittinirundorn, Supawit; Suksom, Pakaun; Suksom , Daroonwan (Journal of Sports Science and Health, 2025)
Exercise provides significant benefits for patients with obesity by reducing the risk of comorbidities that contribute to premature mortality. Typically, there are three primary forms of exercise recommended for individuals with obesity: aerobic exercise, resistance exercise, and flexibility exercises. Currently, numerous studies have investigated the effectiveness of various forms of exercise, with a particular focus on promoting weight loss, reducing body fat, preserving lean muscle mass, and enhancing energy metabolism. According to a review of previous studies, high-intensity interval training (HIIT) has been shown to be effective in improving cardiorespiratory fitness, reducing body fat, and requiring less time compared to continuous moderate-intensity exercise. Subsequently, research has examined concurrent exercise modalities, such as aerobic exercise with resistance training and HIIT with resistance training. These combined approaches have demonstrated superior outcomes in terms of weight loss, fat reduction, and muscle mass preservation compared to single-mode exercise interventions. This article aims to gather various beneficial exercise modalities for individuals with obesity, providing a guideline for developing the most appropriate and effective exercise programs.